(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Corn is one of the world’s most popular cereals and a staple food source in many countries. Corn is the third most important food crop in India, after rice and wheat. Corn is also used as a food and a raw material in industry. It is highly cultivated multipurpose cereal, is grown in a variety of varieties around the world. The current study was designed to examine the physico-chemical properties of five different varieties of corn. The chemical properties of corn seeds were determined using five different corn varieties. The physico-chemical properties of corn are very important to determine the nutritional quality of grains. Moisture (%), Ash (%), Crude Fat (%), Crude Fibre, Crude Protein (%), Carbohydrate (%), and Starch (%) are the physico-chemical properties of corn. There was significant variation observed in physico-chemical properties 9.10-10.06%, 1.32-1.85%, 6.75-7.05%, 5.04-6.54%, 8.06-9.86%, 65.37-69.09%, and 63.68-67.95%respectively.